A European randomised controlled trial of the addition of etoposide to standard vincristine and carboplatin induction as part of an 18-month treatment programme for childhood (≤16 years) low grade glioma – A final report. (August 2017) - Gnekow, Astrid K.; Walker, David A.; Kandels, Daniela; Picton, Susan; Giorgio Perilongo; Grill, Jacques; Stokland, Tore; Sandstrom, Per Eric; Warmuth-Metz, Monika; Pietsch, Torsten; Giangaspero, Felice; Schmidt, René; et al.
Abstract: Background: The use of chemotherapy to manage newly diagnosed low grade glioma (LGG) was first introduced in the 1980s. One randomised trial has studied two- versus four-drug regimens with a duration of 12 months of treatment after resection. Methods: Within the European comprehensive treatment strategy for childhood LGG, the International Society of Paediatric Oncology–Low Grade Glioma (SIOP LGG) Committee launched a randomised trial involving 118 institutions and 11 countries to investigate the addition of etoposide (100 mg/m 2, days 1, 2 & 3) to a four-course induction of vincristine (1.5 mg/m 2 × 10 wkly) and carboplatin (550 mg/m 2 q 3 weekly) as part of 18-month continuing treatment programme. Patients were recruited after imaging diagnosis, resection or biopsy with progressive disease/symptoms. Some 497 newly diagnosed patients (M/F 231/266; median age 4.26 years (interquartile range (IQR) 2.02–7.06)) were randomised to receive vincristine carboplatin (VC) (n = 249) or VC plus etoposide (VCE) during induction (n = 248), stratified by age and tumour site. Findings: No differences between the two arms were found in term of survival and radiological response. Response and non-progression rates at 24 weeks for VC and VCE, were 46% versus 41%, and 93% versus 91% respectively; 5-year Progression-Free Survival (PFS) and Overall Survival (OS) were 46% (StDev 3.5) versus 45% (StDev 3.5) and 89% (StDev 2.1) versus 89% (StDev 2.1) respectively. Age and diencephalic syndrome are adverse clinical risk factors for PFS and OS. 5-year OS for patients in early progression at week 24 were 46% (StDev 13.8) and 49% (StDev 16.5) in the two arms, respectively. Interpretation: The addition of etoposide to VC did not improve PFS or OS. High non-progression rates at 24 weeks justify retaining VC as standard first-line therapy. Infants with diencephalic syndrome and early progression need new treatments to be tested. Future trials should use neurological/visual and toxicity outcomes and be designed to discriminate between the impact on disease outcomes of 'duration of therapy' and 'age at stopping therapy'. Highlights: A randomised trial in the commonest brain tumour type in children – low grade glioma. Tumour response assessment at 6 months identifies those at greatest risk of subsequent progression and death. Intensifying induction treatment with etoposide does not improve progression-free survival. International consortium successfully recruits from 11 European countries in a childhood brain tumour. Carboplatin hypersensitivity is reduced by coadministration of etoposide.